Subjectivity and Synchrony in Artistic Research: Ethnographic Insights - Schindler, Johanna (transcript, 2018)
Artistic research has become an established mode of inquiry and knowledge production in many fields. Johanna Schindler examines the collaborative practices of two artistic research projects in the fields of digital musical instrument design and responsive environments. How are individual research modes organized? Which forms of knowledge are at stake? And what sort of influence do institutional settings, spatial arrangements, and boundary objects have on the emerging research dynamics?Schindler's ethnographic study explores these questions and suggests concrete measurements that can be utilized to adapt the research environments, funding structures, and evaluation criteria of artistic research projects to the specific needs of this emerging field.